Best evidence summary on sexual health management for patients undergoing intracavitary brachytherapy for gynecological neoplasms - Liu, Rui; Fan, Zhanxin; Ma, Hailong; Ye, Jianyan; Chen, Liqing; Qin, Meirong; Wang, Lin (Frontiers in Oncology, 2026)
ObjectiveTo systematically retrieve, appraise and synthesize the best available evidence on sexual health management in patients undergoing intracavitary brachytherapy for cervical cancer, so as to provide an evidence-based foundation for developing individualized sexual-health care plans in clinical practice.MethodsA comprehensive computer-based search of domestic and foreign databases, guideline repositories and professional association websites was conducted for all evidence on sexual health management in cervical-cancer patients receiving intracavitary brachytherapy. Document types included guidelines, evidence summaries, systematic reviews, expert consensus statements and clinical decision aids. The search timeframe spanned database inception to June 2025.ResultsTwelve publications were ultimately included: two clinical decision aids, one guideline, four systematic reviews, two evidence summaries, one expert consensus and two randomized controlled trials. Thirty-nine evidence statements were extracted and grouped under seven themes: target population and risk factors, screening and assessment, health education, non-pharmacologic interventions, pharmacologic and hormonal therapies, special treatments, and follow-up.ConclusionThis study summarizes the best current evidence on sexual health management for cervical-cancer patients undergoing intracavitary brachytherapy and offers valuable guidance for improving patients’ quality of life and sexual-health outcomes.Systematic Review Registrationhttp://ebn.nursing.fudan.edu.cn/home, identifier ES20256976.